The Effect of Work Efficiency on Employee Work Productivity During the Covid 19 Virus Pandemic (Case Study in the Operational Division of Pt Pelindo Daya Sejahtera Surabaya) - Bachtiar J. Helmy; Wahyu Arief Santoso; Dwi Widi Hariyanto (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2020)
PT. Pelindo Daya Sejahtera Surabaya is one of the ousourching companies that manages outsourcing professionals in a professional manner and the operational division is one of the most affected divisions with the covid virus - 19. In order to achieve conditions of maintaining and even increasing work efficiency and work productivity, the implementation of work from home ( Work From Home) is an option for some employees. To determine the relationship of the independent variable (work efficiency) to the dependent variable (work productivity) the saturation sampling method of 30 employees is used with the analysis tool is simple multiple linear regression. From the results of the study indicate that work efficiency has a significant effect on employee productivity in operational divisions and the results of the coefficient of determination show that work efficiency has an effect of 65.3% on employee work productivity during the co-19 virus pandemic.